SOSIALISASI PENERAPAN AKTIVITAS MENGGAMBAR DAN MERIAS DIRI TERHADAP PENURUNAN TANDA DAN GEJALA PADA PASIEN HARGA DIRI RENDAH DI WILAYAH KERJA UPTD PKM KONCARA - Grace Evelyn; Dina Hartini; Dini, Dini (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
Low self-esteem is a self-concept disorder that often occurs in patients with mental disorders and psychosocial problems. This condition is characterized by feelings of worthlessness, lack of self-confidence, and withdrawal from the social environment. Non-pharmacological efforts that can help improve self-esteem are through drawing and make-up activities, which can stimulate self-expression and strengthen a positive body image. To determine the effect of implementing drawing and make-up activities on reducing signs and symptoms in patients with low self-esteem in the work area of ​​​​the UPTD PKM Koncara. This community service activity aims to improve the knowledge and skills of nurses in the work area of ​​​​the UPTD PKM Koncara Purwakarta Regency in implementing drawing and make-up activities to reduce signs and symptoms in patients with low self-esteem. The method of implementation of the activity used a lecture and demonstration approach. The activity participants were 20 people consisting of nurses. Evaluation was carried out using a pre-test and post-test to assess the increase in knowledge, as well as observation of skills during simulation practice. The results of the activity showed an increase in participants' knowledge from an average value of 58% (pre-test) to 89% (post-test). Furthermore, 90% of participants were able to simulate chest compressions and artificial ventilation using the correct technique. Participants also demonstrated high enthusiasm in participating in all activities. Socialization of the application of drawing and make-up activities to reduce signs and symptoms in patients with low self-esteem was proven effective in increasing nurses' knowledge and skills in reducing signs and symptoms of low self-esteem. This therapy can be used as an alternative nursing intervention in group activity therapy programs in community health facilities